1997
DOI: 10.1103/physrevb.55.15494
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and charge ordering inPr1xCa

Abstract: The orbital and charge ordering in Pr 1−x Ca x MnO 3 (x=0 and 0.5) from the ab initio calculations

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Concerning the theory, several groups have argued as to the dominant mechanism leading to the stability of the CE-type phase, but the basic picture has not been questioned [15,16,17,18,19]. However, ab initio calculations predict a noninteger mixed valence accompanying an orbitally ordered CEtype phase in half-doped manganites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the theory, several groups have argued as to the dominant mechanism leading to the stability of the CE-type phase, but the basic picture has not been questioned [15,16,17,18,19]. However, ab initio calculations predict a noninteger mixed valence accompanying an orbitally ordered CEtype phase in half-doped manganites.…”
Section: Introductionmentioning
confidence: 99%
“…However, ab initio calculations predict a noninteger mixed valence accompanying an orbitally ordered CEtype phase in half-doped manganites. For Pr 0.5 Ca 0.5 MnO 3 , Anisimov et al [15] showed that two different Mn e g configurations exist which have almost the same charge density with different orbital configurations. The COO is predicted to be of the checkerboard type, one site having a 3x 2 − r 2 -type symmetry, the other a x 2 − y 2 -type symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…We find a ground state with A-type antiferromagnetic order and an insulating gap. The gap results from a lifting of the degeneracy between the quarter-filled e g states that accompanies the in-plane orbital ordering (and driven by the large on-site repulsion [10,11]). These findings are consistent with the actual ground state of LaMnO 3 .…”
mentioning
confidence: 99%
“…Also further-neighbour superexchange terms, that should destabilize other phases like a conventional two-sublattice antiferromagnet, might well have to be included to make the CE structure the most stable one near x = 1/2. But then one should use a multi-band model and perhaps also different values for in-plane and out-of-plane hopping amplitudes, in view of the in-plane orientation of the e (1) g orbital and orbital ordering [24,49,50]. Indeed, such models might well be required to remove the near symmetry about x = 1/2 in our phase diagram (figure 7), which is not seen in experiments.…”
Section: Discussionmentioning
confidence: 99%